Women Leaders and Resilience: Reducing Poverty in Developing Countries, Indonesia - Elly Nurlia; Luki Oka Prastio; Ombi Romli (Government & Resilience, 2023)
Environmental issues are indeed a global conversation. In the Asian region, environmental issues are a priority in various countries. One of the countries in Asia that is concerned with environmental issues is Indonesia. Indonesia as a developing country considers environmental issues to be very important, why is it important because it is part of the welfare of the community in accordance with the mandate of the 1945 Constitution. The existence of a female leader, is she capable of her feminine instincts to make important decisions through her programs as a leader in dealing with poverty problems? Absolutely, the issue of poverty will have a lot of impact on women themselves, for example because of poverty, often the case of mothers who die when giving birth to their babies because of very minimal health workers. The presence of female leaders gives a lot of hope in development in Indonesia, especially in disadvantaged areas. Women leaders are expected to be able to contribute greatly in reducing and alleviating poverty in Indonesia. This study used a qualitative method with a case study approach; the location of this study was in a disadvantaged area, Lebak District, Banten Province.